Measuring junior high school students’ science learning and science process skills through an ıntegrated science ınstructional assessment - Sukardıyono; Rosana, Dadan; Dwandaru, Wipsar Sunu Brams (Journal of Turkish Science Education, 2019)
This study aimed to produce a valid and reliable assessment tool for junior high school students’ integrated science learning and determine their improvement of science process skills (SPS) using the integrated science instruction. The research procedure consisted of ten stages, i.e., preliminary study, planning, development of draft assessment tool, validation of draft assessment tool, first revision of draft version, pilot study, second revision (stage II), operational field tests, third revision (stage III), and dissemination. The Aiken V formula was utilized to obtain instrument’s validity, whilst interclass correlation coefficients were calculated for its reliability. The results showed that the instructional assessment was valid with lowest (0.89) and highest (0.98) validity values. The reliability coefficients of the first, second and third observation sheets were found to be 0.93, 0.94 and 0.92, respectively, which fell into a very good category. This means that these observation sheets were feasible for measuring SPS. The results indicated that the students’ SPS levels were very good for predicting, experimenting, observing, and measuring, while ‘concluding and communicating’ aspects were good.